Pre-transport dietary chitosan improves the physiological robustness of juvenile largemouth bass (Micropterus salmoides) by modulating antioxidant and inflammatory responses - Hong-Zheng Zhao; Yu-Lin Chang; Chang Wang; Yu-Yun He; Yi-Ran Zhao; Yi-Chen Dong; Xu-Xiong Huang; Guo-Fang Zhong (Fish & Shellfish Immunology, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

A validated field-to-model framework for pesticide residue prediction and dietary risk assessment in pear production - Ran Yi; Chen Chen; Nan Huang; Xinquan Wang; Yanhua Wang; Jing Wang (Food Control, 2026)

Ultraconductive carbon film/fiberboard heterostructure integrating superior EMI shielding and efficient joule heating - Ziyi Yin; Ran Wang; Yansong Wang; Yi Hou; Yang Hu; Shiyue Tang; Zhijiang Wang; Xiaolin Lan; Zhanhua Huang (Chemical Engineering Journal, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Synergistic effects of co-pyrolyzed rice straw/non-woven fabric biochar on soil enhancement and rice growth promotion - Shuo Su; Jiachen Zhu; Tian Xie; Zhihua Zhang; Yi Zhu; Yu Xie; Yuting Ran; Lingling Yao; Jie Qin; Jing Huang; Junxin Zhou; Zhi Zhou; et al. (Paddy and Water Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Quantity and quality decoupling in soil carbon sequestration: A case study focusing on the stability of soil organic matter in reclaimed coal gangue soils - Fei Wang; Ran Zhao; Kang Zhao; Yi-Zong Huang; Feng Xu (Journal of Environmental Sciences, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Active intermediate water-mediated kinetic promotion for synergistic solar evaporation and photocatalytic mineralization - Xuanting Li; Jinchi Li; Xinrong Huang; Qian Chen; Xinyu Li; Hongbing Wang; Jiang Gong; Ran Niu; Yi Lu; Xiaoke Li (Chemical Engineering Journal, 2026)

Interplay of fracture roughness and wettability on immiscible displacement under favorable conditions: A lattice Boltzmann simulation with an improved wetting treatment - Han Huang; Yi-Feng Chen; Zhibing Yang; Ran Hu; Jia-Qing Zhou (Advances in Water Resources, 2026)

Leveraging industrial symbiosis benefits from multi-source heavy metal hazardous waste co-reutilization with industry kilns for anthropogenic metal recovery: Methods and applications - Long Wen; Luying Xiao; Yi Yao; Zhisong Ran; Yang Yue; Xiaojia Chen; Beijia Huang; Yao Wang (Journal of Cleaner Production, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A LLM-based agent for the construction of typhoon knowledge graphs - Yi Huang; Yongqi Xia; Ran Tao; Donglai Jiao; Xiangqiang Min; Jieying Zheng; Yuting Jiang; Wenjun Wu; Peijun Du (Environmental Modelling & Software, 2026)

Seaward expansion of mangrove wetlands in the Dafeng Estuary, Beibu Gulf from 1988 to 2022 - Yi Chen; Zhijun Dai; Xuefei Mei; Hu Huang; Mingquan Cai; Yangyang Xi; Ran Chen (Marine Environmental Research, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Machine Learning Improves Mesoscale Offshore Wind Resource Assessment over the Yellow Sea - Haixing Gong; Kan Yi; Dinghua Yang; Wenyu Huang; Chenqing Fan; Ran Hao; Lina Sha; Mengke Deng; Hao Zhang (Journal of Meteorological Research, 2025)

Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China - Yi-RAN Huang; Yu-Cheng Wang; Xiao-Xuan Meng; Yu-Tao Xiang (Science Bulletin, 2025)

Tea saponin assisted micellar extraction combined with in-situ aqueous two phase enrichment of flavonoids and lactones from functional food - Si-Yi Liu; Xin-Ran Ma; Qian-Xue Shen; Huang-Fei Jin; Jun Cao (Food Research International, 2025)

Impact of tris (2-chloropropyl) phosphate and triphenyl phosphate on honeybee (Apis mellifera L.) midgut health: Assessing toxicity and potential mitigation with melatonin - Rongyi Ye; Yihan Wang; Kebo Wang; Ran Yi; Fengjiao Sun; Nan Huang; Tianliang Zhang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Study on the influence mechanism of endogenous protein components on the characteristics of distiller's grains starch - Min Huang; Li Li; Xinran Cheng; Ran Qiu; Yi Wang; Xianjiang Zhou; Xuyan Zong (Food Chemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Evaluating the combined toxicity of broflanilide and myclobutanil on honeybees (Apis mellifera L.): Molecular mechanisms and protective effects of curcumin - Rongyi Ye; Ran Yi; Yihan Wang; Nan Huang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Efficient mining of natural products from Mangrove streptomyces using NP-PRESS - Lin Yu; Junxiao Wang; Kai Jin; Fan Xu; Yi Huang; Ran Zhang; Yihan Wu; Fei Xu (Archives of Microbiology, 2025)

Soil health assessment of urban forests in Nanchang, China: Establishing a minimum data set model - Fei Huang; Jiamei Tu; Foyi Zhang; Jingwang Ran; Yi Wang; Wei Liu; Wenxuan Chen; Xinyao Wang; Qiong Wang (Soil Biology and Biochemistry, 2025)

Electrochlorination Fenton-like and Fenton processes for different categories of phosphonates oxidation to orthophosphate: Performance and mechanism characteristics - Sainan Sun; Guanghua Huang; Jiawei Tang; Fazhi Xie; Xiao Wang; Qiang Guo; Hongshuai Kan; Meng Qiao; Yanpeng Liu; Yi Liu; Zixiao Zhu; Xu Zhao; et al. (Journal of Hazardous Materials, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Suspended sediment (SPS) triggers nitrogen retention by altering microbial network stability and electron transport behavior during the aerobic-anoxic transition - Xiaoyan Liu; Tingting Pei; Guojia Xu; Tinglin Huang; Yaoguo Wu; Xiaowei Jin; Yi Cao; Ran Sun; Sihai Hu; Pathmalal M. Manage; Xiang Liu; Tao Liu; et al. (Journal of Environmental Management, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Yi-fan Xiang; Da-juan Wan; Chen-ran Wang; Jun-lin Huang; Xue-ying Cao; Jia-qi Chen; Ning-xiang Ouyang (Environmental Monitoring and Assessment, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

The legacy effects of soil types on carbon content are erased by extreme flooding stress in a water-level drawdown zone - Yiguo Ran; Shengjun Wu; Yi Jiang; Junfeng Qu; Imali Kaushalya Herath; Ping Huang (CATENA, 2023)

Exercise preconditioning promotes myocardial GLUT4 translocation and induces autophagy to alleviate exhaustive exercise-induced myocardial injury in rats - Yuan-Pan Guo; Shan-Shan Pan; Tian-Ran Chen; Yue Huang; Dong-Feng Wan; Yi-Shan Tong (Journal of Molecular Histology, 2023)

Particulate matter, nitrogen dioxide, and sulfur dioxide and their associations with allergic skin diseases: A systematic review and meta-analysis - Jin Huang; Wen-hao Zheng; Hong-chan Huang; Yi-guo Ran; Yi Liu; Ping Huang (Atmospheric Pollution Research, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Effects of wind–wave disturbances on adsorption and desorption of tetracycline and sulfadimidine in water–sediment systems - Qianjiahua Liao; Zheng Huang; Shu Li; Yi Wang; Yuqing Liu; Ran Luo; Jingge Shang (Environmental Science and Pollution Research, 2018)

Long-term agronomic practices alter the composition of asymbiotic diazotrophic bacterial community and their nitrogen fixation genes in an acidic red soil - Weibing Xun; Wei Li; Ting Huang; Yi Ren; Wu Xiong; Youzhi Miao; Wei Ran; Dongchu Li; Qirong Shen; Ruifu Zhang (Biology and Fertility of Soils, 2018)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process - Jian-Jun Yang; Meng-Xi Huang; Qian-Yi Wu; Hao-Ran Zhang (Contributions to Mineralogy and Petrology, 2014)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Active surveillance of renal masses in von Hippel-Lindau disease: growth rates and clinical outcome over a median follow-up period of 56 months - Jin Zhang; Jia-Hua Pan; Bai-Jun Dong; Wei Xue; Dong-ming Liu; Yi-Ran Huang (Familial Cancer, 2012)

Functional analysis of pig myostatin gene promoter with some adipogenesis- and myogenesis-related factors - Bing Deng; Jianghui Wen; Yi Ding; Qishuang Gao; Haijun Huang; Zhiping Ran; Yunguo Qian; Jian Peng; Siwen Jiang (Molecular and Cellular Biochemistry, 2012)